Evaluation of rail services - Cole, Stuart; Holvad, Torben; O'Higgins, Thaddaeus; Gommers, Michael (Proceedings from the Annual Transport Conference at Aalborg University, 1997)
Rail services are needed for basic mobility especially in rural areas and as a mean of reducing congestion and pollution as part of an integrated transport policy in urban areas. In transport expenditure generally there may be a number of options open but in the case of train passenger services there are essentially three: a) to retain the service in its present form, b) to close the service, c) to rationalise the network (by amending merging routes). The only railway likely to be profitable is one where there is an intensive use with high load factors. This is never going to be so for rural railways or on large commuter rail systems. This places the evaluation of such services into the political context.Therefore, it is important to identify the impacts generated from rail services and to determine the social value these represent. This information provides an objective basis for decisions on public funding of rail services. The paper is planned as follows. Section 1 discusses the role of rail services. In section 2 examples of currently used evaluation techniques and criteria are described. This is followed by an examination of a potential approach to the evaluation of rail services, section 3. Section 4 discusses practical issues in relation to the approach outlined. Finally, section 5 summarises the findings and gives suggestions for further research.